2007
DOI: 10.1016/j.eatbeh.2006.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Religion, weight perception, and weight control behavior

Abstract: Religion's relationships with weight perception and weight control behavior were examined using data (3032 adults aged 25-74) from the National Survey of Midlife Development in the United States. Religion was conceptualized as denomination, religious attendance/practice, religious social support, religious commitment, religious application, and religious identity. Weight perception was conceptualized as underestimating body weight, overestimating body weight, and accurately assessing body weight. Respondents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 62 publications
3
52
0
2
Order By: Relevance
“…As values and perceptions are the leading indicators of the external behavior and performance of organizations as well as individuals (Parker et al, 2003;Kim, 2007;Larsman et al, 2012), the poor CSR performance of CICs can be attributed to their inadequate CSR values and perceptions. According to Waldman et al (2006), China ranks very low with regard to CSR values compared to other countries.…”
Section: Introductionmentioning
confidence: 99%
“…As values and perceptions are the leading indicators of the external behavior and performance of organizations as well as individuals (Parker et al, 2003;Kim, 2007;Larsman et al, 2012), the poor CSR performance of CICs can be attributed to their inadequate CSR values and perceptions. According to Waldman et al (2006), China ranks very low with regard to CSR values compared to other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Religion appears to be especially salient for black women and has been shown to play an important role in health and disease management (Holt & McClure, 2006;Chatters, 2000). Recent studies have reported a relationship between religion and weight, as well as religion and body image (Cline & Ferraro, 2006;Kim, 2007;Ferraro, 1998). These studies suggest that in contrast to the wider society, religious individuals may place less emphasis on the physical body and use their relationship with a higher power and/or the ability to meet moral/religious obligations to evaluate self-worth (Kim, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…16 International studies have found disturbances of this nature to be more prevalent in Jewish adolescent girls and women than in their non-Jewish counterparts. [17][18][19] The emergence of data suggesting that Jewish girls and women may be at an increased risk of developing eating disorders [17][18][19] 2014;27(4) S Afr J Clin Nutr is of concern to the global Jewish community. Food is often seen to be a focal point of Jewish traditions, spanning cultural, ethnic and religious paradigms.…”
Section: Introductionmentioning
confidence: 99%